DRILL INJECTED TECHNOLOGY APPLICATION EXPERIENCE FOR THE PURPOSE OF GROUND REINFORCEMENT AND PILE ERECTION DURING RECONSTRUCTION - Ihnatov, S. V. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The drill injected technology for pile erection and shallow foundations strengthening implementation in practice is described in the article. The reconstruction of the building, the topography and geotechnical conditions of the building footprint analysis are presented. The article reveals the design solutions for reconstruction of existing building for industrial purposes, and describes the basic technological processes. It is considered design scheme of the building, the results of the spatial frame calculation, the substantiation of bases slab base strengthening necessity provided design solutions for building new above-ground building structures. The article describes the case of pile foundations for the elevator shaft building, the description of the technical solutions in piling, the results of piled-raft foundation settlement observations, which was loaded by the loads from the walls and ceilings of mine and lifting equipment. The paper discloses the design of technical solution for existing slab base of special technology foundation strengthening, the technology of amplification, as well as the results of experimental and control sensing.
Keywords: injection; settlement; foundation; pile; test; observation; the raft